The Effect of Health Education Peer Group Model on IVA Test Examination Attitudes in Women of Childbearing Age in Klayu, Tegalwaru, Jember - Prastika , Niken Dwi; Hidayati, Ainul; Karnasih, I Gusti Ayu (Journal of Nursing Periodic, 2024)
Introduction. Early detection of cervical cancer is an effort to examine the condition of the cervix as early as possible by conducting an IVA (Visual Inspection of Acetic Acid) test, especially women who have been actively having sex. The purpose of this study was to analyze the effect of health education peer group model on IVA test examination attitudes in women of childbearing age in Klayu, Tegalwaru, Jember. This research design is pre-experiment design using One Group Pretest and Posttest design. Methods: The population in this study amounted to 110 respondents. With a sample of 86 respondents using probability sampling techniques by means of cluster random sampling. Statistical test using Fisher's Exact Test. Result: The results of the attitudes of women of childbearing age before being given the health education peer group model showed negative attitude categories as much as (73.3%) and positive attitudes as much as (26.7%). The attitude of women of childbearing age after being given a health education peer group model experienced a change in attitude, in the positive category as much as (97.7%) and negative attitudes (2.3%). Statistical tests using SPSS 24 Fisher Exact Test obtained p-value results of 0.025 <(0.05). Conclusions: With the health education peer group model can improve the attitude of women of childbearing age towards IVA test examination. The occurrence of changes in women of childbearing age to IVA test examination is because women of childbearing age already know and understand the purpose and benefits of IVA test examination which is explained through the peer group model.